Advanced Role of Neutrophils in Common Respiratory Diseases. (15th May 2017) - Liu, Jinping; Pang, Zhiqiang; Wang, Guoqiang; Guan, Xuewa; Fang, Keyong; Wang, Ziyan; Wang, Fang
Abstract : Respiratory diseases, always being a threat towards the health of people all over the world, are most tightly associated with immune system. Neutrophils serve as an important component of immune defense barrier linking innate and adaptive immunity. They participate in the clearance of exogenous pathogens and endogenous cell debris and play an essential role in the pathogenesis of many respiratory diseases. However, the pathological mechanism of neutrophils remains complex and obscure. The traditional roles of neutrophils in severe asthma, chronic obstructive pulmonary diseases (COPD), pneumonia, lung cancer, pulmonary fibrosis, bronchitis, and bronchiolitis had already been reviewed. With the development of scientific research, the involvement of neutrophils in respiratory diseases is being brought to light with emerging data on neutrophil subsets, trafficking, and cell death mechanism (e.g., NETosis, apoptosis) in diseases. We reviewed all these recent studies here to provide you with the latest advances about the role of neutrophils in respiratory diseases.